Fermentative profile, chemical composition, in vitro gas production and ruminal degradation kinetics of sugarcane silages associated with different levels of butterfly pea hay - Nascimento Ramos, Ery J; Souza Almeida, Bruno A; Costa Gois, Glayciane; Ribeiro Menezes, Daniel; Ribeiro Silva, Ana P; Santos Nunes, Timóteo S; Ávila Queiroz, Mário A (Revista Colombiana de Ciencias Pecuarias, 2023)
Background: The ensiling process of sugarcane promotes yeast proliferation during fermentation, requiring the use of additives. Clitorea ternatea can be used as a natural additive in sugarcane silages to reduce dry matter losses and modifying the fermentation profile of the silage. Objective: To evaluate the fermentative profile, chemical composition, in vitro gas production and ruminal degradation kinetics of sugarcane silages associated with different levels of butterfly pea hay. Methods: Increasing levels of butterfly pea hay (0, 10, 20, and 30% on dry matter basis) were added to sugarcane silages. A completely randomized design was adopted, with four treatments and four repetitions, totaling 16 experimental silos that were opened after 60 days of ensiling. Results: Positive changes were observed in terms of fermentative losses, fermentative profile, chemical composition, in vitro gas production, and ruminal degradation kinetics with the addition of butterfly pea hay to sugarcane silage (p<0.05). Conclusion: The inclusion of up to 20% butterfly pea hay in sugarcane silage reduces fermentation losses and improves silage quality, such as increase in protein and energy content and reduction of the fibrous fractions of the silage, making silage an excellent ingredient to be included in ruminant diets.